2021
DOI: 10.2478/emj-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Intangible assets and the efficiency of manufacturing firms in the age of digitalisation: the Russian case

Abstract: A wide consensus exists on the role of intangible assets in both developed and developing economies, especially now, with the new generation of information and communication technologies. Emerging economies generally demonstrate lower endowment with intangibles (Dutz et al., 2012), but follow the same positive patterns for long-run development. In Russia, the contribution of intangibles to growth is still modest, and its capacity to foster productivity has not been achieved. As previous studies showed, efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…A study by Turovets (2021) further emphasized this transition, examining the impact of intangible assets on Russian manufacturing firms (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). Despite a currency crisis, the synergy between intangible assets and knowledge accumulation enhanced technical efficiency, particularly in high-tech firms.…”
Section: Uncertainty Contextsmentioning
confidence: 99%
“…A study by Turovets (2021) further emphasized this transition, examining the impact of intangible assets on Russian manufacturing firms (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). Despite a currency crisis, the synergy between intangible assets and knowledge accumulation enhanced technical efficiency, particularly in high-tech firms.…”
Section: Uncertainty Contextsmentioning
confidence: 99%
“…At the same time, retail demand for frozen and packaged foods has increased significantly (OECD, 2020). Turovets (2021), in his research stated that working capital management is one of many approaches that use tangible assets as a proxy for company performance and concluded that only a few studies have explored intangible assets as a predictor of company efficiency. Based on the Resource-based theory, companies gain competitive advantage and superior performance through acquisitions using strategic assets (Wernerfelt, 1984).…”
Section: Introductionmentioning
confidence: 99%